Language Challenges Faced by International Graduate Students in the United States - Kuo, Ya-Hui (Journal of International Students, 2011)
Universities and colleges in the United States require international graduate students to provide certain English proficiency documents along with their admission applications before they are admitted to their programs.This study explored the language challenges faced by international graduate students at a Southern university in the U.S. The author also offered recommendations and suggestions to prepare and assist international graduate students in adjusting, adapting, and overcoming their language challenges.